Comunicación y biblioteca - Pirnuta, Oana-Andreea (Revista General de Información y Documentación, 2003)
This article analyses the library’s function in the field of communication, library services, the shaping of the human personality with introductions to the peculiarities of different age groups such as children, adolescents, young people and reading, older people and information culture. Emphasis is given to creativity in library activities, communication and public relations within the library framework.